Multidisciplinary analysis of the prognosis and biological function of NUBPL in gastric cancer - Liu, Luqian; Zhang, Fengyu; Yu, Jiaye; Dong, Pingping; Deng, Jing; Liu, Weiwei; Cao, Xinlei; Huang, Juanjuan; Lin, Xiaoming; Xue, Xiangyang (Frontiers in Immunology, 2025)
BackgroundResearchers are currently concentrating on molecular markers and potential therapeutic targets associated with gastric cancer in light of recent developments in precision medicine and molecular biology. Disulfidptosis was first proposed in 2023 as a novel programmed cell death mode associated with the cytoskeleton. Disulfidptosis-related proteins are essential for the preservation of protein stability and abnormal expression of disulfidptosis-related genes may be linked to cancer development and drug resistance.Materials and methodThe gastric cancer transcriptomic data were retrieved from TCGA database, and disulfidptosis-related genes were identified through literature search. Utilizing machine learning methods such as LASSO, Random Forest (RF), Boruta, SVM-RFE, and XGBoost, the disulfidptosis-related gene NUBPL was determined as a potential predictor for gastric cancer. PPI network was constructed, and the GO database as well as the KEGG database were employed to analyze the protein interactions and pathway enrichment of NUBPL in gastric cancer. Meanwhile, the ESTIMATE algorithm was used for immune infiltration analysis and prediction of immunotherapy response, and the Genomics of Drug Sensitivity in Cancer (GDSC) database was utilized for the drug sensitivity analysis of NUBPL. The role of NUBPL in gastric cancer and its inhibition of disulfidptosis were validated using molecular biological methods.ResultsThe aberrant expression of NUBPL significantly impacts the prognosis of gastric cancer and modulates metabolic and immune-related pathways. In patients with elevated NUBPL expression levels, a reduced number of CD8-positive T cells is associated with adverse prognosis and gastric cancer progression. Elevated NUBPL expression levels can impair the function of chemokines. Moreover, patients with lower NUBPL expression levels exhibit better responses to immunotherapy. We have also identified drugs such as QS11, Imatinib, and AS601245 as potential inhibitors of NUBPL. In vitro experiments have shown that NUBPL affects the invasion and migration of gastric cancer cells, rather than proliferation and apoptosis, by regulating the PPP pathway and inhibiting disulfidptosis.ConclusionThis study underscores the pivotal role of NUBPL in gastric cancer progression and highlights its significance as a potential target for targeted therapy and immunotherapy gastric cancer, NUBPL, disulfidptosis, biomarker, immunotherapy, machine learning